2020
DOI: 10.1021/acs.jafc.0c00986
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Proteomics and Metabolomics Analysis Highlights Correlative Metabolite-Protein Networks in Soybean Seeds Subjected to Warm-Water Soaking

Abstract: Soaking of soybean seeds is a prerequisite for the production of soy foods, and it has been shown that the extent of water absorbed during different imbibition conditions directly affects the quality of the subsequent soybean seed products by yet unknown mechanisms. In order to elucidate the molecular changes in soybean seeds during different soaking temperatures, we performed an integrated proteomics and metabolomics analysis of seeds soaked at 4, 25, and 55 °C. Proteomics analysis revealed that various enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 53 publications
(97 reference statements)
0
16
0
Order By: Relevance
“…Moreover, a previous report revealed that LAPs related to various major metabolism in filling and matured stages of soybean seeds were successfully enriched and identified in PS-S fraction using TMT-based quantitative analysis (Min et al 2020b). Therefore, here we utilized the PS precipitation method in combination with TMT-based quantification to identify the differential proteins from the seeds of Daewon and Saedanbaek differing in total protein contents (Gupta et al 2020;Min et al, 2020aMin et al, , 2020b. This approach led to the identification of 1,146 significantly modulated proteins (FDR < 0.05, FC > 1.5) by the comparison between Daewon and Saedanbaek cultivars.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, a previous report revealed that LAPs related to various major metabolism in filling and matured stages of soybean seeds were successfully enriched and identified in PS-S fraction using TMT-based quantitative analysis (Min et al 2020b). Therefore, here we utilized the PS precipitation method in combination with TMT-based quantification to identify the differential proteins from the seeds of Daewon and Saedanbaek differing in total protein contents (Gupta et al 2020;Min et al, 2020aMin et al, , 2020b. This approach led to the identification of 1,146 significantly modulated proteins (FDR < 0.05, FC > 1.5) by the comparison between Daewon and Saedanbaek cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the PS-S fraction was dissolved in 80% acetone containing 0.07% β-mercaptoethanol and stored -20°C until further analysis. Trypsin digestion by filter-aided sample preparation (FASP), TMT labeling and peptide pre-fractionation by basic pH reverse phase chromatography were carried out as described previously (Gupta et al 2020;Kim et al 2018;Min et al 2020a;Wiśniewski et al 2009). A total of 12 peptide fractions were collected, lyophilized in a vacuum centrifuge and stored at -80°C until further LC-MS/MS analysis.…”
Section: Plant Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Omics approaches in those studies were often used separatelyproteomics and metabolomics-and an integrated analysis using these approaches was rarely conducted in fish nutrition. Thus, in order to provide more metabolic information to explain the relationship between dietary nutrition and fish growth, it was necessary to combine metabolomics with proteomics in nutritional studies with fish (Guo et al, 2019;Min et al, 2020;Yu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%